2021
DOI: 10.1109/access.2021.3100105
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Attention Over LSTM With Bayesian Optimization for Day-Ahead Solar Power Forecasting

Abstract: The penetration of PVs into the power grid is increasing day by day, as they are more economical and environment-friendly. However, due to the intrinsic intermittency in solar radiation and other meteorological factors, the generated power from PVs is uncertain and unstable. Therefore, accurate forecasting of power generation is considered one of the fundamental challenges in power system. In this paper, a deep-learning model based on two-stage attention mechanism over LSTM is proposed to forecast a day-ahead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“… ( Aslam et al, 2021 )where o i and pi are the observed and predicted MIC, respectively, and n indicates the number of datasets.…”
Section: Methodsmentioning
confidence: 99%
“… ( Aslam et al, 2021 )where o i and pi are the observed and predicted MIC, respectively, and n indicates the number of datasets.…”
Section: Methodsmentioning
confidence: 99%
“…DL/ML models are state-of-the-art tools that predict and interpret AMR [ 28 ]. These models map input features to the target labels in non-linear relationships [ 29 ]. The objective is to do regression or classification, or in some cases interpretation of the outcomes [ 28 , 30 ].…”
Section: Artificial Intelligence (Dl/ml) For Antimicrobial Resistancementioning
confidence: 99%
“…K-mers are also assigned labels with respective phenotypes and perform the encoding [ 32 ]. Data pre-processing and encoding and feature extraction all can easily be implemented using different Python packages [ 29 ]. Different machine-learning and statistical tools can also be used to generate important features.…”
Section: Artificial Intelligence (Dl/ml) For Antimicrobial Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Due to great advantages in solving complex nonlinear problems, artificial intelligence models have been favored by many researchers. Aslam et al proposed a deep-learning model based on a two-stage attention mechanism over long short-term memory networks (LSTM) for forecasting day-ahead solar power [10]. Although the introduction of an attention mechanism can improve the prediction performance of the neural network, its calculation is complicated, which may cause the model to converge slowly.…”
Section: Introductionmentioning
confidence: 99%